A STUDY OF GREEN HUMAN RESOURCE MANAGEMENT PRACTICES IN HIGHER EDUCATIONAL INSTITUTES IN MUMBAI - Bhatt, Jay; Oak, Amit P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There is a growing awareness among the people about the environmental sustainability due to the pressure brought by various social activists & the government policies to prevent the degradation of the environment. Green human resource management is one tool of achieving sustainable environment. Educational institutions can be an instrumental in spreading greater awareness about the green practices through their educational programs. The present research is being conducted in the higher educational institutions to understand the green human resource management being adopted in these institutions. The focus of the research is on three important variables namely green recruitment and selection, green training and development & green performance appraisal. The research was based on a sample of 50 teaching staff. The findings of the research revealed that the mean score of GHRM for recruitment & selection was 1.75, for green training & development it was 1.76 & for performance appraisal it was 1.53. The low score indicates that the organisations green human resource management practices are not well aligned with the environment sustainability. The low mean score indicates the need for emphasizing & integrating green practices into the human resource management functions of the organisation especially recruitment, selection, training & development & performance appraisal.